Strategi Nafkah Keluarga Buruh Tani: Studi Pola Nafkah Ganda dan Rekayasa Spasial di Desa Rea Kabupaten Poewali Mandar - Nurannisa Lumanto; Firdaus W. Suhaeb (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2022)
This research was conducted with the aim of knowing (1) what factors encourage women to work as farm laborers (2) how to form a family livelihood strategy for farm workers in a double income and spatial engineering pattern in Rea Village, Polewali Mandar Regency. This type of research is descriptive qualitative research with a qualitative approach, determining the subject using purposive sampling technique. Data analysis techniques used are data reduction, data presentation and drawing conclusions that are directly related to the research problem. The results of this study indicate that (1) the factors that encourage women to work as farm laborers are two factors, internal and external factors. Internal factors are family income, educational background. External factors consist of environment and culture, meaning that there is an invitation from family, neighbors to participate in working as laborers. (2) The form of livelihood strategies carried out by the families of farm workers. The first is the dual income pattern apart from being farm laborers, the family of farm workers doing work outside the agricultural sector and the work of family members in earning a living for father, mother and children, while working as motorcycle taxi drivers, construction workers, fishing and raising livestock. Migration carried out by families of farm laborers is by doing work outside their village, working outside the area such as construction workers, daily farm laborers.